EVALUASI KINERJA PT. PINDAD (Persero) DENGAN BALANCED SCORECARD (Studi Kasus Pada PT. Pindad (Persero)) - , Diah Andari ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research proposes will ask about performance evaluation PT. Pindad (Persero) with the Balanced Scorecard. Related to the performance of companies in the financial perspective, customer perspective, internal business process perspective, and learning and growth perspectives. Evaluation of the Financial Perspective so from the perspective of the financial performance of the organization is good, but there are some indicators that realization is not in accordance with the targets set by the organization. Evaluation Customer Perspective so from the perspective of the organization's performance has been good customer it can be seen from the achievement of the targets set targets by the organization. But with the indicators on the actual perspective of the authors noticed that the indicators do not show the customers' satisfaction. Evaluation of Internal Business Process Perspective. So from the perspective of internal business process performance has been good organization it can be seen from the target achievement targets set by the organization. Follow-up of the fraud and the number of cases pending and needs to be done early before deviation resulted in losses in the future. And will also significantly affect the company's business continuity. Evaluation of Learning & Growth Perspective. So from the perspective of organizational learning and growth performance has been good it can be seen from the achievement of the targets set targets by the organization.